The Impact of Preoperative Patient Education on Postoperative Pain, Opioid Use, and Psychological Outcomes: A Narrative Review - Rasheeda Darville-Beneby; Anna M. Lomanowska; Hai Chuan Yu; Parker Jobin; Brittany N. Rosenbloom; Gretchen Gabriel; Helena Daudt; Michael Negraeff; Tania Di Renna; Maria Hudspith; Hance Clarke (Taylor & Francis Group, 2023)
ABSTRACTBackground Recent studies have shown that preoperative education can positively impact postoperative recovery, improving postoperative pain management and patient satisfaction. Gaps in preoperative education regarding postoperative pain and opioid use may lead to increased patient anxiety and persistent postoperative opioid use.Objectives The objective of this narrative review was to identify, examine, and summarize the available evidence on the use and effectiveness of preoperative educational interventions with respect to postoperative outcomes.Method The current narrative review focused on studies that assessed the impact of preoperative educational interventions on postoperative pain, opioid use, and psychological outcomes. The search strategy used concept blocks including "preoperative" AND "patient education" AND "elective surgery," limited to the English language, humans, and adults, using the MEDLINE ALL database. Studies reporting on preoperative educational interventions that included postoperative outcomes were included. Studies reporting on enhanced recovery after surgery protocols were excluded.Results From a total of 761 retrieved articles, 721 were screened in full and 34 met criteria for inclusion. Of 12 studies that assessed the impact of preoperative educational interventions on postoperative pain, 5 reported a benefit for pain reduction. Eight studies examined postoperative opioid use, and all found a significant reduction in opioid consumption after preoperative education. Twenty-four studies reported on postoperative psychological outcomes, and 20 of these showed benefits of preoperative education, especially on postoperative anxiety.Conclusion Preoperative patient education interventions demonstrate promise for improving postoperative outcomes. Preoperative education programs should become a prerequisite and an available resource for all patients undergoing elective surgery.